2022
DOI: 10.1590/fst.02622
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological study of the effect of a dielectric barrier discharge interaction on processed orange juices exposed to the environment

Abstract: Non-pasteurized juices may contain microorganisms that cause spoilage and public health problems. Owing to their physical properties, dielectric barrier discharge plasmas show high efficiency in the inactivation of microorganisms; in this study, coliforms, Escherichia coli and Salmonella spp. were identified in samples of orange juice collected from street stalls. Microbiological inactivation in orange juice was analyzed using the Weibull model. Using optical emission spectroscopy, the oxidant particles respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The treatment of orange juice with dielectric barrier discharge plasmas for 2.5, 3.5, 5.0 and 6.0 min with electrical power of 40 W showed a reduction in Salmonella spp. colony forming units of 4.47 to 1.00 Log and from 4.00 to 1.00 Log for E. coli (Ocaña de Jesús et al, 2022). Liao et al (2018) also reported that, after treatment with plasma DBD in apple juice, it had a slight effect on the °Brix, pH, titratable acidity, color values, total phenolic content and antioxidant capacity of this product.…”
Section: Physicochemical Properties and Bioactive Compounds During St...mentioning
confidence: 88%
See 1 more Smart Citation
“…The treatment of orange juice with dielectric barrier discharge plasmas for 2.5, 3.5, 5.0 and 6.0 min with electrical power of 40 W showed a reduction in Salmonella spp. colony forming units of 4.47 to 1.00 Log and from 4.00 to 1.00 Log for E. coli (Ocaña de Jesús et al, 2022). Liao et al (2018) also reported that, after treatment with plasma DBD in apple juice, it had a slight effect on the °Brix, pH, titratable acidity, color values, total phenolic content and antioxidant capacity of this product.…”
Section: Physicochemical Properties and Bioactive Compounds During St...mentioning
confidence: 88%
“…For such purpose, it is used a plasma in which the energy of the electrons is much higher than the other species. Since the plasma has a more chemical character and it is obtained at atmospheric pressure is known as cold atmospheric plasma (Ocaña de Jesús et al, 2022).…”
Section: Physicochemical Properties and Bioactive Compounds During St...mentioning
confidence: 99%